124. Acute Uncomplicated Cystitis in Urgent Care Centers: Changes in Antibiotic Prescribing Practices Before and After Provider Education. (31st December 2020) - Cofsky, Rebecca S; Goodman, David; Morton, Arianna; Powell, Debra L; Blanchard, Edward
Abstract: Background: Acute uncomplicated cystitis (AUC) is a frequent infection that requires antibiotic treatment that is seen in women who seek care at urgent care centers. 1 The Infectious Diseases Society of America (IDSA) has published guidelines for the management of AUC. They recommend nitrofurantoin, trimethoprim-sulfamethoxazole, or fosfomycin as the first-line agents for the treatment of AUC in healthy adult women. 1 Previous evaluation of prescribing practices at Tower Health Urgent Care Centers demonstrated a 16% compliance rate with treatment guidelines for AUC. Subsequently, provider education and an AUC medication order set in the electronic medical record (EMR) were implemented. The purpose of this study was to evaluate the effectiveness of these interventions on prescribing practices for AUC. Methods: A retrospective electronic chart review was performed evaluating the antibiotic treatment of patients diagnosed with AUC between January 1, 2018, to June 30, 2019, excluding July 2018 to September 2018, the washout period during which education was provided. Inclusion criteria included age ≥ 18 years, female, and treated at one of three Tower Health Urgent Care Centers. Results: 1, 455 patients met inclusion criteria during our study period. Our three-month washout period included 273 of those patients. 421 patients were included in the pre-education analysis with 761 patients in the post-education analysis. When both first and second-line antibiotic prescriptions were evaluated in conjunction with considering patient allergies and concomitant infections, compliance was 59% in our post-education analysis (improved from 16% compliance at baseline). Conclusion: Provider education and an AUC medication order set in the EMR were successful in increasing the compliance rate with antibiotic treatment guidelines for the management of AUC in adult females in the urgent care setting. Disclosures: All Authors : No reported disclosures